Diffusion in silicon : a seven-year retrospective - Fisher, D. J. (Diffusion and defect data. Defect and diffusion forum, 2005)
This collection of abstracts of experimental and theoretical papers on the subject of diffusion in silicon is intended to complement earlier volumes (DDF153-155) which covered the previous decade's work on the same topic. The abstracts are grouped according to the diffusing species in question. The latter comprise Ag, Al, As, Au, B, Ba, Be, C, Ca, Cl, Co, Cr, Cu, Er, F, Fe, Ge, H, He, Hf, In, Ir, K, Mg, Mn, Mo, N, Na, Nb, Ni, O, P, Pb, Pt, Rb, Sb, Se, Si, SiH3, Sn, Ti, V, Yb and Zn with regard to bulk diffusion, Ag, Au, Ba, Cl, Cu, Er, F, Ga, Ge, In, O, Pb, Sb, Si, SiH3, Sn and Y with regard to surface diffusion, H with regard to grain-boundary diffusion, and self-diffusion in liquid Si. In a separate section, diffusion in SiGe alloys is covered. The work on bulk diffusion here involves the diffusants: As, Au, B, Cu, Ge, H, Li, P, Sb or Si. Overall, this succinct up-to-date guide to the topic of diffusion in silicon will be useful to anyone involved in the theory, development or processing of silicon-based semiconductors.